PENINGKATAN KUALITAS DESAIN SABLON DI DESA POGAR KECAMATAN BANGIL KABUPATEN PASURUAN - Listin Fitrianah; Agus Rachmad Purnama; Machfudzil Asror (Journal of Science and Social Development, 2019)
This dedication supports the design of screen printing as a means of increasing the production of screen printing at the screen printing partner diploma provided in Pogar Village, Bangil District, Pasuruan Regency. So far the designs are made only from consumer demand and no one has specifications and graphic designs. This activity uses a controversial method that is providing theoretical material first and followed by a workshop directly making screen printing products produced by partners. The results of the training showed that the participants were very happy and happy to be able to participate in this activity. Participated in training and wanted to master how to design (85%). Participants and employees can enjoy the benefits of using practical methods in making screen printing designs, presenter and teams more easily provided knowledge and developing screen printing design potential.